A reciclagem química como alternativa ao tratamento de resíduos plásticos no Brasil - Avelino, Guilherme Monteiro (Universidade Federal de São Carlos, 2020)
Recycling is a process carried out in the transformation of products. This can be done mechanically, chemically and energetically. In each of the defined types there are different processes, as well as the final products and raw materials. Given this, the present study sought to understand the challenges that gasification, as a chemical recycling methodology, faced in Brazil and how they can be overcome so that this method is a viable alternative with mechanical recycling, in order to improve waste treatment plastics in our country. To this end, the study started from a bibliographic review about mechanical recycling and chemistry in Brazil, critically analyzing some processes and the variables that involve them, in addition to discussing the social, economic and environmental impacts that each treatment has. The results obtained allowed us to conclude that mechanical recycling is the main recycling resource carried out in Brazil. Mechanical recycling is financially more effective when compared to the other two types of recycling practiced, in addition to providing employability in the sector. It was also found that reverse logistics, guaranteed by law, allows the right destination for the treatment of solid waste, and should be further explored. However, it must be considered that mechanical recycling has variables that hinder its use, since certain plastic residues cannot be recycled by this processing. Thus, investment in chemical recycling is necessary, but the financial demand that it requires is understood. Sustainability is highlighted as a major factor in this scenario, and should be considered in the different recycling processes. Finally, it is concluded that gasification, explored by the researcher in this study, presents itself as an alternative for the treatment of plastic waste, thus, the need for further exploratory studies in the researched area is stated.
Chemical Recycling as an Alternative to the Treatment of Plastic Waste in Brazil.
Keywords: Reciclagem; Reciclagem Química; Reciclagem Mecânica; Gaseificação; Resíduos Plásticos; Recycling; Chemical Recycling; Mechanical Recycling; Gasification; Plastic Waste; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA